The politics of anti-Westernism in Asia visions of world order in pan-Islamic and pan-Asian thought - Aydin, Cemil (Columbia studies, 2007)
In this intellectual history, Cemil Aydin challenges the notion that anti-Westernism in the Muslim world is a political and religious reaction to the liberal and democratic values of the West. Nor is anti-Westernism a natural response to Western imperialism.